The Potential Contribution of Dental Foci and Oral Mucositis to Febrile Neutropenia in Patients Treated With Myelosuppressive Chemotherapy for Solid Tumors and Lymphoma - Zecha, Judith A. E. M.; Raber-Durlacher, Judith E.; Laheij, Alexa M. G. A.; Westermann, Anneke M.; de Lange, Jan; Smeele, Ludi E. (Frontiers in Oral Health, 2022)
Introduction Febrile neutropenia (FN) is a potential life-threatening complication of myelosuppressive chemotherapy, particularly when induced by infection. There is evidence that FN can originate from the oral cavity, but its contribution to FN is largely understudied in patients treated for solid tumors. The aim of this study was to assess the prevalence of FN in these patients and to evaluate its relation with dental foci and oral mucositis. Material and Methods A prospective longitudinal observational study was conducted. Patients diagnosed with solid tumors and lymphoma scheduled to be treated with myelosuppressive chemotherapy with an intermediate risk of developing FN were included. A pre-chemotherapy dental examination was performed and patients were followed during and after chemotherapy regimen. During subsequent hospital visits for chemotherapy administration, the oral cavity was inspected and oral mucositis (OM) was scored using the CTC-AE version 3.0. When patients presented with fever, a comprehensive full body examination including laboratory/microbiological/imaging investigation was performed. Results Eighty-eight patients were included. Pre-chemotherapy, 39 patients (44.3%) were diagnosed with a dental focus. During chemotherapy, 46 patients developed OM (53.4%), of which 15 patients had a maximum score of grade II (ulcerative mucositis). Ten patients developed FN during the follow-up period. Patients with FN more often suffered from ulcerative OM compared to patients without FN; both FN and mucositis risk was associated with the myelotoxicity of chemotherapy. However, no relation could be established between the presence of dental foci prior to chemotherapy and the development of FN (p > 0.05). Conclusion A significant relation was identified between ulcerative OM and FN, but no robust conclusions could be drawn with respect to a relationship between the presence of dental foci and FN.